Development of the Potty Fun Kid’s Digital Media Application to Improve Toilet Training Independence in Children with Autism Spectrum Disorder - Hoiriyah, Hoiriyah; Priyanti, Nita; Imamah, Imamah (Universitas Islam Negeri Jurai Siwo Lampung, 2025)
This study aims to develop and evaluate the effectiveness of the digital application “Potty Fun Kid’s” in enhancing toilet training independence among children with autism spectrum disorder (ASD). A pre-test–post-test design was employed involving 26 children with ASD enrolled in an inclusive school. The application was validated by media experts and subject matter experts prior to its six-week implementation as an intervention. Data were collected through observations of toilet training independence, questionnaires completed by teachers and parents, and semi-structured interviews. The findings revealed a significant increase in toilet training independence scores, from a pre-test mean of 152.88 (categorized as “moderately independent”) to a post-test mean of 231.35 (categorized as “independent”). Potty Fun Kid’s was rated as highly feasible by both media and subject matter experts, achieving a feasibility score of 90%. The majority of teachers and parents (92.9%) reported improvements in children’s toilet training independence, particularly in recognizing signs, following sequences, and communicating toileting needs. The visual schedule and reward system features were identified as the most effective components of the application. Observational data indicated an increase in successful toilet use rates from 40% to 100% and a reduction in dependence on assistance. In conclusion, Potty Fun Kid’s is effective in promoting toilet training independence among children with ASD by ensuring a consistent approach between school and home environments.